Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jnnfm.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Fully-resolved simulations of particle-laden viscoelastic fluids using an immersed boundary method

Abstract: This study reports the development of a direct simulation code for solid spheres moving through viscoelastic fluids with a range of different rheological behaviors. The numerical algorithm was implemented on an opensource finite-volume solver coupled with an immersed boundary method, and is able to perform fully-resolved simulations, wherein all flow scales associated with the particle motion are resolved. The formulation employed exploits the log-conformation tensor to avoid high Weissenberg number issues whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 65 publications
(132 reference statements)
2
25
0
Order By: Relevance
“…Significant effort has been expended on improving the accuracy of embedded boundary schemes [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], an overview is provided in [18]. In addition, methods which build on the IB or Immersed Finite Element (IFEM) method but with modifications such as the use of one-sided interpolation and spread operators near to boundaries have been used to model flow past fixed objects and deformable particles in a viscoelastic fluid [41][42][43]; these works have shown that averaged flow features are resolved but convergence of the stress at and near boundaries is not considered. A subset of these improved embedded boundary methods [18,19,39] generate solutions to the fluid equations that are globally smooth in a simple domain, and as such allow discretizations of more complicated, nonlinear equations to be constructed in a way that is nearly unaltered from solvers used on simple geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effort has been expended on improving the accuracy of embedded boundary schemes [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], an overview is provided in [18]. In addition, methods which build on the IB or Immersed Finite Element (IFEM) method but with modifications such as the use of one-sided interpolation and spread operators near to boundaries have been used to model flow past fixed objects and deformable particles in a viscoelastic fluid [41][42][43]; these works have shown that averaged flow features are resolved but convergence of the stress at and near boundaries is not considered. A subset of these improved embedded boundary methods [18,19,39] generate solutions to the fluid equations that are globally smooth in a simple domain, and as such allow discretizations of more complicated, nonlinear equations to be constructed in a way that is nearly unaltered from solvers used on simple geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In those cases, instead of using Equation (A1), a different variation of the method could be used. Assuming that ap was the order of accuracy of the discretization schemes used in the calculation procedure, instead of using three meshes, the extrapolated value could be obtained by Equation (A1) using only the two most refined meshes [32].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The flow of particle-laden complex fluids has been the centerpiece of many well-documented experimental, theoretical, and numerical approaches [ 1 , 2 , 3 , 4 ]. These fluids are non-Newtonian in character showing shear thinning, shear thickening, viscoplastic, time-dependent and viscoelastic behaviors under different flow conditions.…”
Section: Introductionmentioning
confidence: 99%